2019
DOI: 10.1016/j.injury.2019.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Fracture repair in the elderly: Clinical and experimental considerations

Abstract: Fractures in the elderly represent a significant and rising socioeconomic problem. Although aging has been associated with delays in healing, there is little direct clinical data isolating the effects of aging on bone healing from the associated comorbidities that are frequently present in elderly populations. Basic research has demonstrated that all of the components of fracture repair -cells, extracellular matrix, blood supply, and molecules and their receptors-are negatively impacted by the aging process, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…In rodent models, an age‐associated dysregulation in inflammatory response to fracture injury is well documented (Baht et al, 2018) as we previously reviewed. Although aging has been associated with delays in healing in humans, there are little direct clinical data isolating the effects of aging on bone healing from the associated comorbidities that are frequently present in older adult populations (Meinberg et al, 2019). The increased risk of premature death after fracture in the geriatric population confounds the ability to compare rates of fracture healing in older and younger adults due to survivor bias.…”
Section: Discussionmentioning
confidence: 99%
“…In rodent models, an age‐associated dysregulation in inflammatory response to fracture injury is well documented (Baht et al, 2018) as we previously reviewed. Although aging has been associated with delays in healing in humans, there are little direct clinical data isolating the effects of aging on bone healing from the associated comorbidities that are frequently present in older adult populations (Meinberg et al, 2019). The increased risk of premature death after fracture in the geriatric population confounds the ability to compare rates of fracture healing in older and younger adults due to survivor bias.…”
Section: Discussionmentioning
confidence: 99%
“…As the geriatric population increases, a better understanding of how bone healing changes with age is crucial for developing effective treatment strategies and providing better medical care for these patients. The risk of non-unions increases with age, and osteoporotic fractures are associated with higher morbidity and mortality rates and increased costs for the health care system [2][3][4][5]. This has been proven in different in vivo animal models, and it was shown that cartilage and bone formation, resorption, bone microporosity, bone marrow stem cell function and quantity, as well as vascular perfusion of femoral blood flow was altered in old animals [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…There are many challenging issues for any type of ORIF in the elderly, which often include a combination of decreased soft tissue quality, prior scar tissue, poor bone stock, and joint stiffness of the affected limb. The same age-related comorbidities that compromise fracture healing (e.g., diabetes, malnutrition, osteoporosis, osteopenia, and polypharmacy including chronic opioid use) increase the complexity level of operative fracture treatment and after-care in the elderly [ 7 , 9 , 18 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whether age is an independent risk factor for nonunion remains unclear. There is evidence that bone repair is delayed in the elderly compared to younger patients [7][8][9]. Recent studies (animal and human) elucidated small but potentially important differences between fracture healing in these two age groups [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation